Preliminary experimental insights into differential heat impact among lithic artifacts (Journal of Lithic Studies, 2016)
The presence of thermally altered and broken flint artifacts is common at archaeological sites. Most studies focus their attention on the effects of heat treatment on flint to improve knapping qualities, disregarding the effects of fire over flint under uncontrolled conditions. This paper aims to show how under uncontrolled heating processes flint artifacts develop different heat alterations (such as levels of breakage, presence of scales, etc.) as a result of vertical distribution, volume or raw material and to establish a gradient of rock changes and behavior. Artifacts where macroscopically analyzed and a series of uncontrolled heating experiments through the distribution of flint blanks under two hearths were carried out, allowing a comparison of the before and after of the blanks. Preliminary results show how levels of breakage, surface alteration or development of heat alteration features can be differentiated according to artifact volume, vertical distribution and level of surface alteration. Results also show how two different raw materials react differently to similar thermal impact, and how surface alteration reacts at different rhythm in the case of recycled artifacts. We conclude that levels of thermal alteration can be differentiated through macroscopic analysis of flint surface.